Immune complexes inhibit differentiation, maturation, and function of human monocyte-derived dendritic cells - Laborde, Evangelina Andrea (2007)
The interaction between immune complexes (IC) and the receptors for the Fc portion of IgG (Fc Rs) triggers regulatory and effector functions in the immune system. In this study, we investigated the effects of IC on differentiation, maturation, and functions of human monocyte-derived dendritic cells (DC). When IC were added on day 0, DC generated on day 6 (IC-DC) showed lower levels of CD1a and increased expression of CD14, MHC class II, and the macrophage marker CD68, as compared with normally differentiated DC. The use of specific blocking Fc R mAbs indicated that the effect of IC was exerted mainly through their interaction with Fc RI and to a lesser extend with Fc RII. Immature IC-DC also expressed higher levels of CD83, CD86, and CD40 and the expression of these maturation markers was not further regulated by LPS. The apparent lack of maturation following TLR stimulation was associated with a decreased production of IL-12, normal secretion of IL-10 and CCL22, and increased production of CXCL8 and CCL2. IC-DC displayed low endocytic activity and a reduced ability to induce allogeneic T cell proliferation both at basal and LPS-stimulated conditions. Altogether, these data reveal that IC strongly affect DC differentiation and maturation. Skewing of DC function from Ag presentation to a proinflammatory phenotype by IC resembles the state of activation observed in DC obtained from patients with chronic inflammatory autoimmune disorders, such as systemic lupus erythematosus disease and arthritis. Therefore, the altered maturation of DC induced by IC may be involved in the pathogenesis of autoimmune diseases.